2018
DOI: 10.1266/ggs.18-00039
|View full text |Cite
|
Sign up to set email alerts
|

Increased population epigenetic diversity of the clonal invasive species <i>Alternanthera philoxeroides</i> in response to salinity stress

Abstract: Epigenetic modification can change the pattern of gene expression without altering the underlying DNA sequence, which may be adaptive in clonal plant species. In this study, we used MSAP (methylation-sensitive amplification polymorphism) to examine epigenetic variation in Alternanthera philoxeroides, a clonal invasive species, in response to salinity stress. We found that salinity stress could significantly increase the level of epigenetic diversity within a population. This effect increased with increasing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…This is imperative for invading new, heterogeneous ecosystems. For instance, a study of the clonal invader Alternanthera philoxeroides (alligator weed) found that under salinity stress, epigenetic diversity within a population was significantly increased [79]. Similar results were found when studying Reynoutria japonica (Japanese knotweed) another clonal invader [80].…”
Section: Epigeneticsmentioning
confidence: 55%
“…This is imperative for invading new, heterogeneous ecosystems. For instance, a study of the clonal invader Alternanthera philoxeroides (alligator weed) found that under salinity stress, epigenetic diversity within a population was significantly increased [79]. Similar results were found when studying Reynoutria japonica (Japanese knotweed) another clonal invader [80].…”
Section: Epigeneticsmentioning
confidence: 55%
“…According to the available reports, salinity undoubtedly changes the pattern of DNA methylation in plant genomes. This finding was confirmed by studies conducted on a clonal plant Alternanthera philoxeroides where the variation in the methylation patterns increased under the influence of salt stress [30]. The majority of the literature reports DNA hypermethylation under salt stress.…”
Section: Plos Onementioning
confidence: 56%
“…Epigenetic modifications are considered an alternative mechanism by which plants withstand stress without changing nucleotides in the DNA sequence (Kinoshita & Seki, 2014; Kovalchuk et al, 2003; Meyer, 2015; Shi et al, 2018). The MASP technique has been shown to be an effective molecular tool that can be used in plants with little genome data sequence information (Li et al 2011, Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Here we present the results of a study conducted with flax -an agricultural crop grown for six generations under chronic radiation stress and attempted to determine whether years of exposure to an Epigenetic modifications are considered an alternative mechanism by which plants withstand stress without changing nucleotides in the DNA sequence (Kinoshita & Seki, 2014;Kovalchuk et al, 2003;Meyer, 2015;Shi et al, 2018). The MASP technique has been shown…”
Section: Discussionmentioning
confidence: 99%